Gamificação nas práticas pedagógicas : um desafio para a formação de professores em tempos de cibercultura - Martins, Cristina (2015)
This thesis, associated to the Graduate Program in Education at the Pontifícia Universidade Católica do Rio Grande do Sul, in the line of research on Training, Policies and Practices in Education, discusses the challenges of teachers’ formation to work with cyberculture, where the school and university system preserves outdated paradigmatic heritages. Moreover, new meanings aimed at the complete education of the student are necessary. Our guiding question is as follows: what are the relations between the development of educational gamified practices and the formation background of teachers in the Early Years of Elementary Education in a private school in Porto Alegre/RS? The objective was to investigate how the formation background of professors of Early Years (EY) of Elementary Education (EE) in a private school in Porto Alegre/RS implies the constitution of educational practices based on gamification, based on the proposal of a model of elements of digital games in gamified activities. The theoretical foundation consisted of the state of the knowledge, where the following authors highlighted: Tardif, Lévy, Huizinga, Santaella, Alves, Zabala and Arnau, and, Prensky. For the research methodology, we opted for a qualitative approach, using a case study. The data analysis was carry out using Textual Discourse Analysis, using the following data collection instruments: questionnaires, participant and non-participant observations, interviews and research journals. The research subjects were professors of EY in EE. The main results show that: (a) the initial formation rarely enables the professor to develop the competencies necessary for working with cyberculture; (b) the short-term continuing education courses do not provide the teacher with the necessary reflection and experiences; (c) the teachers that include gamification in their teaching practices do not always understand what they are doing; (d) the model proposed is promising, though the teachers that present the best results are those who have already had contact with Role-Playing Games and with gamification elements. The following issues remain to be discussed in future research: broadening the investigation to other environments and pursuing contributions of gaming to student learning.